Análisis de los determinantes y costos de la informalidad en las peque\~nas empresas: Un estudio empírico para el Perú; Analysis of determinants and costs of informality in small businesses: An empirical study for Peru - Brenda Liz Silupu Garcés; Sergio David Reyes Landa (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
– Informality in small businesses is a widespread phenomenon in Latin American countries. In Peru it represents 50% of the business units, a situation that implies the knowledge of the determinants of this reality to contribute to the design of public policies. Thus, the present work studies the variables related to the productive performance and the life quality of the company owner's home as elements highly related to informality. In addition, it is evaluated whether the employer's decision about informality responds to a maximization of profits or, on the contrary, it is due to exclusion because the current legislation is apart from the real nature of the business unit. The conclusions allow observing that the characteristics of the home facilitate the formality and that the existing tax regulatory framework excludes small companies, which experience lower levels of profit compared to formal companies with similar characteristics.
Keywords: M13; M21; H26; 330; exclusion; taxes; profits; probability